Keunggulan Tartil Al Qur’an melalui Metode Ummi di SMK Al Kautsar - Abdullah Al Hasyir; Heni Ani Nuraeni (Syntax Corporation Indonesia, 2024)
Reading The Qur'an With Tartil Is An Obligation For Every Muslim. Therefore Muslims Are Required To Improve The Reading Of The Qur'an Well And Accurately With The Right Rhythm. Of Course Tartil Reading Requires A Method, And One Of These Methods Is The Ummi Method. This Method Includes Tartil Reading According To Tajweed Rules By Emphasizing The Love Of Systematic And Practical Reading Methods To Be Learned Applying Sequential Reading. This study discusses the advantages of reading Tartil Al-Qur'an Ummi method for Class X students of SMK Al Kauthar Jakarta. By Using Qualitative Research, This Study Tries To Introduce And Provide Knowledge About Practical And Systematic Methods In Learning To Read The Qur'an. The Main Data Sources Of This Study Are Islamic Religious Education Teachers And Religious Teachers. Primary Data sources from Reference Book of ummi method secondary research include previous research Data, bibliography Book of Ummi method. Data collection techniques the results of this study are the advantages of tartil Al quran through the method of Ummi diSMK Al kautsar Jakarta in increasing the quality in reading the quran is located from the quality system, a simple system, easy to understand and quality. There is also a comparison of some of the same methods used to learn to read the quran but don’t same with ummi method